Gibberellic acid supplements mitigate the sodium chloride effects on onion seed germination and its physio-chemical attributes - Haq, Ikram-Ul; Gill, Nazia Parveen; Yasin, Ghulam; Memon, Sahifa; Soomro, Zainab; Bhatti, Faheem Ahmed; Baloch, Mehwish; Baloch, Chanda Bakhtawar (Universiti Kebangsaan Malaysia, 2023)
The mitigative effect of gibberellic acid (GA3) for salt (NaCl) stresses on seed germination attributes of onion (Allium cepa L.) cultivar Nasarpuri was assessed. Seeds were moisturized with NaCl (0-, 100- and 200-mM) and GA3 (250 ppm) before and after sowing for seed germination in 1st week than in 2nd week, GA3 sprayed once foliarly and NaCl in rooting region. At the end of 1st week, an increase in seed germination rate was observed in seeds supplemented with GA3 from control (85.0%) to 97.5% and from NaCl stressed seeds (72.5% and 50.0%) to 85.0% and 62.5%, respectively (p ≤ 0.05). This reduction in seed germination was caused by salt stresses after 96th hours of sowing, inhibition in GA3-biosynthesis GA3 and delay in α-amylases activation observed in salt stressed seed cultures. The seedling vigor index (SVI) was observed higher in foliarly GA3 sprayed cultures of both control as well as saline stressed cultures. The seedlings supplemented with GA3, decrease in malondialdehyde (MDA), H2O2, Na+/K+, Na+ and Cl- contents, while increases seedling biomass, chlorophyll contents, total proteins, and sugars in NaCl stressed seedlings. Interestingly, GA3 also increased (p ≤ 0.05) the osmoprotectants in seedlings including abscisic acid (AsA), carotenoids, phenolics and proline contents to depict in stress alleviation. This study may be concluded by the fact that GA3 minimizes salinity stresses on seed germination as well as further seedling growth with the increased production of organic osmoprotectants as saline stress neutralizers.